MENINGKATAN HASIL BELAJAR MATEMATIKA PENGERJAAN HITUNG BILANGAN BULAT MENGGUNAKAN METODE LOMPAT KATAK DI KELAS V SD NEGERI KARANGLEWAS KIDUL - Suhartinah (Pusat Studi Pendidikan dan Kreativitas Guru, 2018)
The findings of this study are (1) Teacher action on learning processin cycle II has exceeded indicator 61 that is 71 with good category. (2) Studentlearning outcomes in cycle II with indicator average value of at least 80 has beenfulfilled that is 82,80 and mastery has exceeded 90% that is 96%.